MULTIMEDIA DALAM PENGEMBANGAN LITERASI DI SEKOLAH DASAR TERPENCIL - Tatat Hartati (Universitas Negeri Malang, 2016)
Abstract: This study aims at designing multimedia-based literacy learning model and PAIKEM (Active, Innovative, Creative, Effective, Fun) approach in a remote area of West Java. This research used Research Development approach in two schools within the remote area in Subang and Bandung District Barat. The result of this research showed that teachers in remote areas of West Java require training materials and methods based on PAIKEM literacy and the use of computers for learning media. Computer media used for the training of making a power point and Camtasia studio. Abstrak: Penelitian ini bertujuan merancang model pembelajaran literasi berbasis multimedia dan pendekatan PAIKEM (Pembelajaran Aktif, Inovatif, Kreatif, Efektif, Menyenangkan) di daerah terpencil Jawa Barat. Penelitian ini menggunakan pendekatan, Research Development dengan seting dua sekolah terpencil di Kabupaten Subang dan Kabupaten Bandung Barat.Hasil penelitian menunjukkan bahwa guru-guru di daerah terpencil Jawa Barat memerlukan pelatihan materi dan metode literasi berdasarkan PAIKEM dan penggunaan komputer untuk media pembelajaran. Media computer yang dilatihkan adalah powerpoint dan camtasiastudio.